Wartime Housing as Cultural Landscape: National Creation and Personal Creativity - Evenden, Leonard (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1997)
Early in the 1940s, in response to a housing crisis compounded of lack of construction during the depression, rural to urban migration, and the relocation of labour to the burgeoning wartime industries, dockyards and military bases, the federal government assumed responsibility for the provision of worker housing throughout the country. Construction was initiated through the newly-created crown corporation Wartime Housing Ltd. After some 26,000 rental dwellings were built across the country, the program evolved into veterans' housing. A narrow range of designs (four basic plans) was employed, leading to a image of uniformity, conformity and repetition. A distinctive Canadian residential landscape was thus created, along with a common housing experience. As these dwellings were sold into private hands following the war, modifications were introduced which were integrated into the original simple designs. The appearance of the surviving wartime housing landscapes is nuanced by regional characteristics, but the character of the core units is often still apparent. Authority-based, rational, central planning, a feature of Canada's wartime effort, provided the country with a core stock of dwellings. In half a century a distinctive Canadian residential landscape has evolved from this, with diversity introduced as a result of individual taste, ability to pay, and local regulation.